Sensitive and specific detection of microRNAs by northern blot analysis using LNA-modified oligonucleotide probes - Válóczi, Anna (Oxford University Press, 2004)
We describe here a new method for highly efficient detection of microRNAs by northern blot analysis using LNA (locked nucleic acid)-modified oligonucleotides. In order to exploit the improved hybridization properties of LNA with their target RNA molecules, we designed several LNA-modified oligonucleotide probes for detection of different microRNAs in animals and plants. By modifying DNA oligonucleotides with LNAs using a design, in which every third nucleotide position was substituted by LNA, we could use the probes in northern blot analysis employing standard end-labelling techniques and hybridization conditions. The sensitivity in detecting mature microRNAs by northern blots was increased by at least 10-fold compared to DNA probes, while simultaneously being highly specific, as demonstrated by the use of different single and double mismatched LNA probes. Besides being highly efficient as northern probes, the same LNA-modified oligonucleotide probes would also be useful for miRNA in situ hybridization and miRNA expression profiling by LNA oligonucleotide microarrays.